KINERJA KARYAWAN BERBASIS KEPEMIMPINAN TRANSFORMASIONAL - Tin Isnaini; Heru Sulistyo (Jurnal Ekonomi dan Bisnis, 2011)
The objective of this study is to analize and examine the optimalitation of transformational leadership and its influence on employee performance with employee’s affective commitment, continuans commitment, normative commitment and employee’s creativity variable as intervening variable at Bappeda Kabupaten Jepara. Respondents of this study are all employeesof Bappeda Kabupaten Jepara as many as 50 people, by sampling random sampling methods.With the analytical techniques by using Partial Least Square (PLS).Based on the analysis and discussion in this study obtained a general conclusion that the positive effect of transformational leadership on affective commitment, normative commitment, continuans commitment, and creativity of employees significantly. And affective commitment, normative commitment and commitment kontinuans, and employee creativity positively affected performance significantly.Keyword: transformational leadership, affective commitment, normative commitment, continuans commitment, creativity, performance.